Sistem Informasi Manajemen Ruang Rapat di Universitas Saintek Muhammadiyah Jakarta - Nurfauziah, Habibah; Kadir, Abdul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Muhammadiyah University of Science and Technology needs an efficient management information system to manage meeting rooms in its environment. The management of meeting rooms that has not been done has caused schedule clashes, and delays in the process of borrowing and using meeting rooms. Therefore, this study aims to develop a meeting room management information system that can improve efficiency and effectiveness in managing meeting rooms at Muhammadiyah University of Science and Technology. To improve efficiency and order in managing meeting rooms at Muhammadiyah University of Science and Technology. The method used in this study is a literature study to collect information and understand concepts related to meeting room management systems and system development. This study involves data collection, such as observation, interviews, and needs analysis, to understand the problems and needs of users in meeting room management. The implementation of this system is expected to improve the efficiency of meeting room use, reduce the potential for schedule clashes, and strengthen the communication process between users and related parties. In addition, it is also expected to provide real-time information on meeting room usage and historical data that is useful for further decision making. This study includes the development of a meeting room management information system, system implementation, and testing to ensure the quality and functionality of the proposed system. In addition, an evaluation of the system that has been developed is also carried out to measure its success in increasing efficiency and effectiveness in managing meeting rooms at the Muhammadiyah University of Science and Technology.